Impact of nutrition education on nutritional knowledge, attitude and practices of HIV patients attending ART centre of Susheela Tiwari Hospital, Haldwani, Uttarakhand, India - Baghel SS; Srivastava S; Verma A (International Journal of Life Sciences, 2015)
The study was conducted at ART centre of Susheela Tiwari Hospital, Haldwani, Uttarakhand. The data for the study was collected by personal interview. The impact of nutrition education was assessed by pretested questionnaire before and after imparting nutrition education. The study revealed that majority of the subjects was in the age group 18-60 years. A 10.92 per cent subjects were graduates. The per capita income per month of the subjects was Rs.2125±1512. A significant (p< 0.05) improvement in KAP scores was observed in experimental group subjects while no improvement was seen in the subjects of control group. Gain in KAP scores for knowledge, attitude and practices was 4.89, 3.17 and 1.21, respectively in experimental group while in control group, gain in KAP scores was -0.28, 0.3 and 0.12 for knowledge, attitude and practices, respectively. The differences in gain of KAP scores between control and experimental group was comparable at the baseline but a significant (P<0.05) improvement was seen in case of experimental group after six months. The quantum of improvement in knowledge, attitude and practices was 1.71, 1.08 and 1.20 times, respectively which signified that nutrition education imparted to experimental group resulted in significant (P<0.05) improvement in KAP.